A evolução do Motion Graphics: Da narrativa do cinema para a autonomia audiovisual - Sagatio, Raphael Guaraná (2018)
The way we consume visual information is changed day by day by the hybridization of concepts and forms of communication. Today, virtually all audiovisual devices work with quick animations to inform or just beautify the product to be consumed. These animations are known as motion graphics. The boundaries of audiovisual media are constantly expanding and the aesthetic and informational development is one of the pillars of this way of communicating. With its beginning in the cinema, this work studies the multimodality of motion graphics in the various aspects of the audiovisual sector, focusing on the aesthetic concept, its evolution as a language and as a component in the conduction of the narrative.